Older Adult Self Report Construct and Criterion Validity Evidence for the Brazilian Elderly - Oliveira, Camila Rosa de; Paloski, Luis Henrique; Farina, Marianne; Gonzatti, Valéria; Cunha, Adriano Medeiros; Oliveira, Manoela Ziebell de; Argimon, Irani Iracema de Lima; Irigaray, Tatiana Quarti (Anales de Psicología / Annals of Psychology, 2017)
In Brazil, the number of validated and recognized scientific instruments for clinical evaluation of elderly persons is limited. The Older Adult Self-Report (OASR) is a psychopathological rating scale for persons with more than 60 years, which evaluates adaptive functioning and psychopathology. The aim of this study was at investigating OASR construct and criterion validity evidence for Brazilian elderly. The sample included 345 individuals, between 60 and 94 years of age, which were recruited by convenience. Participants responded to a questionnaire containing questions about demographic and health information, the Mini Mental State Examination, the Geriatric Depression Scale short version and the OASR. Data were analyzed using descriptive statistics, Pearson’s correlation and discriminant analysis. The results showed significant associations between the scores of OASR’s subscales, correlating with general cognitive ability and depressive symptoms. Furthermore, OASR was sensitive to identify elderly with significant symptoms of depression. In conclusion, the OASR showed adequate evidence of construct and criterion validity for a sample of Brazilian elderly.